2016
DOI: 10.1128/jb.00512-16
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Oxidative Stress Induces spxA2 Transcription in Bacillus anthracis Sterne through a Mechanism Requiring SpxA1 and Positive Autoregulation

Abstract: Bacillus anthracis possesses two paralogs of the transcriptional regulator, Spx. SpxA1 and SpxA2 interact with RNA polymerase (RNAP) to activate the transcription of genes implicated in the prevention and alleviation of oxidative protein damage. The spxA2 gene is highly upregulated in infected macrophages, but how this is achieved is unknown. Previous studies have shown that the spxA2 gene was under negative control by the Rrf2 family repressor protein, SaiR, whose activity is sensitive to oxidative stress. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 55 publications
(110 reference statements)
0
8
0
Order By: Relevance
“…In addition to what appears to be a secondary/ back-up role in the activation of oxidative stress responses, global transcriptional analysis suggested that SpxA2 may participate in the regulation of processes associated with cell envelope homeostasis (Kajfasz et al, 2010;. After the initial discovery of two Spx-like regulators in S. mutans, several studies revealed the presence of two Spx paralogs in other streptococci as well as in Listeria monocytogenes and Bacillus anthracis (Turlan et al, 2009;Chen et al, 2012;Barendt et al, 2013;Zheng et al, 2014;Barendt et al, 2016;Port et al, 2017). In addition to the conserved role in activation of oxidative stress responses, Spx regulation has been more recently linked to activation of other types of stress, including antibiotic, osmotic and cell envelope stresses (Renzoni et al, 2011;Jousselin et al, 2013;Baek et al, 2015;Villanueva et al, 2016;Rojas-Tapias and Helmann, 2018a;Nilsson et al, 2019).…”
Section: Transcriptional and Phenotypic Characterizations Of The S Mmentioning
confidence: 99%
“…In addition to what appears to be a secondary/ back-up role in the activation of oxidative stress responses, global transcriptional analysis suggested that SpxA2 may participate in the regulation of processes associated with cell envelope homeostasis (Kajfasz et al, 2010;. After the initial discovery of two Spx-like regulators in S. mutans, several studies revealed the presence of two Spx paralogs in other streptococci as well as in Listeria monocytogenes and Bacillus anthracis (Turlan et al, 2009;Chen et al, 2012;Barendt et al, 2013;Zheng et al, 2014;Barendt et al, 2016;Port et al, 2017). In addition to the conserved role in activation of oxidative stress responses, Spx regulation has been more recently linked to activation of other types of stress, including antibiotic, osmotic and cell envelope stresses (Renzoni et al, 2011;Jousselin et al, 2013;Baek et al, 2015;Villanueva et al, 2016;Rojas-Tapias and Helmann, 2018a;Nilsson et al, 2019).…”
Section: Transcriptional and Phenotypic Characterizations Of The S Mmentioning
confidence: 99%
“…RNA-seq analysis indicated that the expression level of the spxA1 (AW20_RS08630) and spxA2 (AW20_RS25945) genes significantly downregulated in the nprR deletion mutant strain. Both SpxA1 and SpxA2 are closely related to the oxidative stress responses of B. anthracis , and spxA1 is essential for peroxide resistance and participates in disulfide stress tolerance ( Barendt et al, 2013 , 2016 ). SpxA1 is also involved in oxidative stress response of many gram-positive bacteria ( Chen et al, 2012 ; Kajfasz et al, 2017 ; Nilsson et al, 2019 ; Cesinger et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The activity of SpxA2 is regulated at the transcriptional level, in addition to likely regulation by regulated proteolysis. Induction of the operon encoding spxA2 can be activated by either SpxA1 or SpxA2 in response to oxidative stress, such as might be encountered in an activated macrophage (Barendt, Birch, Mbengi, & Zuber, 2016). This induction is needed to overcome the activity of SaiR, which acts as a repressor of spxA2 (M. M. Nakano et al, 2014).…”
Section: Spx Homologs In Bacillus Anthracismentioning
confidence: 99%